Injury-Related Knowledge and Beliefs of Basketball Coaches in Indonesian Setting - Laely Hidayati; Yulia Dwi Setia; Agwin Fahmi Fahanani; Diah Royani Meisani; Djoko Witjaksono; Eko Nugroho (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
As the level of restrictions on community activities (PPKM) decreased, more institutions and organizations began to conduct basketball competitions as a result of the broad popularity of the sport. The intensity of practice has increased as a result of the competitive atmosphere. As a result of increased training intensity, there is an increase in player injuries sustained during practice or competition. This study aimed to explore basketball coaches' beliefs toward injury in student-athletes, particularly at the high school and university levels. The study employed a survey approach, with the target group consisting of basketball coaches at the high school and university levels in Malang, East Java. According to the study's findings, individual factors affecting players put the most significant pressure to play during an injury. Additionally, the coach is the second most influential factor in pressuring injured players to play, trailing only teammates and parents. Among the themes that emerged from this study on injury-related knowledge and beliefs were the determination to win, the significant role of the participants, and the ability to serve as a source of motivation for other players.